Possibility of using fly ash after denitrification by SNCR as admixture in alkali-activated materials. (2021) - Procházka, L.; Mec, P.
Abstract: The paper deals with the possibility of using fly ash including fly ash after SNCR denitrification from power plant Třebovice as an admixture for composites based on alkali-activated blast furnace slag in order to improve selected physical and mechanical properties. Furthermore, the effect of fly ash on hydration and structure influence in thermal analysis was studied. Higher values of flexural strength were achieved in 10% of slag replacement by fly ash. The highest compressive strength values were achieved with blast furnace slag (VGS).